Valorization of Furfural Using Ruthenium (Ii) Complexes Containing Phosphorus-Nitrogen Ligands Under Homogeneous Transfer Hydrogen Condition - Moya-Duran, S; Moya-Duran, S (Elsevier B.V., 2021)
In this paper, we report the catalytic activity of a series of ruthenium (II) complexes containing phosphorus-nitrogen bidentated (P-N) ligands in the hydrogenation of furfural via hydrogen transfer reaction using two hydrogen donor sources: 2-propanol in basic medium and formic acid under mild conditions. The results showed that all the ruthenium complexes studied are catalytically active in the hydrogenation of furfural by hydrogen transfer reaction; they showed 100% conversion with both hydrogen sources. However, selectivities towards the formation of furfuryl alcohol were better when formic acid was used. It was also found that the reaction studied in a basic medium competes with the Cannizzaro reaction, obtaining furfuryl alcohol and furoic acid in a 70/30 ratio; on the other hand, using formic acid as the hydrogen source yields furfuryl alcohol with 100% selectivity. Although formic acid can be used as a hydrogen source successfully. The optimal substrate/acid ratio was found to be 1:1, as a higher concentration of formic acid can cause catalyst decomposition. The yielded products, furfuryl alcohol and furoic acid, obtained from renewable sources, have multiple applications in the organic chemical industry, replacing or complementing similar fossil-derived products. © 2021